A comprehensive review of cyclic activated sludge processes in wastewater treatment: Current perspectives and future challenges - Mohammad Mosaferi; Sakine Shekoohiyan; Ali Behnami; Ehsan Aghayani; Khaled Zoroufchi Benis; Houra Allaeaiea; Mojtaba Pourakbar (Sustainable Chemistry for the Environment)
Recent advances in biological wastewater treatment have spurred the development of innovative modifications aimed at enhancing both efficiency and sustainability. This review examines recent modifications within cyclic activated processes, categorizing them by metabolic function (anaerobic, aerobic, anoxic, and combined), biomass types (attached and suspended growth), and structural changes made to the systems. Cyclic processes demonstrate key advantages, including improved nutrient removal, reduced energy demands, and greater system stability. Nevertheless, challenges persist in optimizing parameters, scaling technology for industrial use, and managing operational costs. The study also investigates the integration of enzymatic processes with cyclic activated sludge, an approach that could significantly enhance the breakdown of organic contaminants. Such combined processes may offer a transformative solution for organic contaminant degradation in wastewater, warranting further research to support their application on an industrial scale. Overall, the ongoing refinement of cyclic activated sludge processes holds considerable promise for advancing sustainable and efficient water treatment technologies, essential for addressing water pollution and conserving resources.